LINGUISTIC SPECIFICATION OF MERONYMY IN ENGLISH AND UZBEK LANGUAGES - Ramazonov Jasur Jalil o'g'li (TADQIQOTLAR, 2025)
Abstract: Meronymy, a semantic relation in which one lexical unit denotes a part, component, or member of a larger whole, plays a crucial role in lexical semantics and cognitive linguistics. This article investigates the linguistic specification of meronymy in the English and Uzbek languages, examining its structural, semantic, and functional properties. Using descriptive, contrastive, and analytical methods, the study analyzes meronymic relations in authentic texts, dictionaries, and corpora, focusing on how part- whole relationships are expressed and conceptualized in each language. The analysis reveals that English and Uzbek share universal cognitive principles in organizing part- whole relations, but they differ significantly in linguistic expression and cultural representation. English often encodes meronymy through concise nominal compounds and prepositional constructions (wheel of a car, branch of a company), whereas Uzbek utilizes morphologically marked, explicit descriptive structures (mashinaning g‘ildiragi, kompaniyaning bo‘limi). These differences reflect both typological distinctions and culturally influenced conceptualizations of part-whole relationships. Furthermore, the study highlights challenges in translation and cross-linguistic interpretation of meronymic relations, emphasizing the importance of semantic, syntactic, and pragmatic awareness.